On the long wave fluctuations in systems of particles interacting with hydrodynamic media - Nikolayenko, S.O.; Slyusarenko, Yu.V. (Вопросы атомной науки и техники, 2012)
Our work offers a stochastic approach for description of long wave fluctuations in systems of particles interacting with hydrodynamic media. The presence of long-wave fluctuations in the system is caused by the random character of external force. The description of fluctuations evolution is based on the averaging of nonlinear dynamic equations over random external force acting on the system. The evolution equations for large scale fluctuations have been derived. The considered system can be a model of neutron transport in hydrodynamic media. We obtain the dynamic equations of long wave fluctuations generated by external random force in hydrodynamic media with multiplication and capture of neutrons and consider the influence of fluctuations over the stability of steady states of such systems. Предложен стохастический подход к описанию длинноволновых флуктуаций в системах частиц, взаимодействующих с гидродинамическими средами. Наличие длинноволновых флуктуаций в системе обусловлено стохастичностью внешней случайной силы. Описание эволюции длинноволновых флуктуаций проводится с помощью метода усреднения нелинейных динамических уравнений по случайной внешней силе. Получены уравнения динамики длинноволновых флуктуаций обусловленных внешней случайной силой в гидродинамических средах с поглощением и размножением частиц. Рассмотренная система может служить моделью переноса нейтронов в гидродинамических средах. Обсуждается вопрос о влиянии флуктуаций на устойчивость стационарных состояний в системе. Запропоновано стохастичний підхід до опису довгохвильових флуктуацій у системах частинок, що взаємодіють із гідродинамічними середовищами. Наявність довгохвильових флуктуацій у системі обумовлено дією випадкової зовнішньої сили. Опис еволюції довгохвильових флуктуацій здійснено за допомогою методу усереднення нелінійних динамічних рівнянь за стохастичною зовнішньою силою. Отримано рівняння динаміки довгохвильових флуктуацій, зумовлених зовнішньою випадковою силою в гідродинамічних середовищах з поглинанням та розмноженням частинок. Розглянута система може бути моделлю переносу нейтронів у гідродинамічних середовищах. Обговорено питання про вплив довгохвильових флуктуацій на стійкість стаціонарних станів в системі.